Determinants of Accounting Implementation Strategies among MUI Halal-Certified MSMEs on Lombok Island: Determinants of Accounting Implementation Strategies among MUI Halal-Certified MSMEs on Lombok Island - Yolanda Destiana; Mandala Faldini (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose:This study aims to identify and analyze the determinants of the strategies implemented by MUI-certified halal MSMEs in the application of accounting on Lombok Island. Design/Method/Approach: This study used a qualitative approach, data was collected through in-depth interviews, observations, and documentation of MUI-certified halal MSMEs. Findings: The research findings indicate that there are several key factors influencing the accounting implementation strategies of SMEs, namely: (1) SMEs in Lombok Island record financial transactions in conducting their businesses, (2) 67% of SMEs on Lombok Island separate personal finances from business finances, (3) 83% of SMEs on Lombok Island create transaction journals and post them to the general ledger, (4) 83% of SMEs on Lombok Island have prepared financial statements. Originality/Values: This study contributes to the development of sharia accounting practices in the SME sector and highlights the importance of continuous mentoring so that halal SMEs can grow sustainably and professionally.